Cavitation enhances coagulated size during pulsed high-intensity focussed ultrasound ablation in an isolated liver perfusion system - Zhao, L; Liu, S; Chen, Z; Zou, J; Wu, F (Taylor and Francis, 2016)
Purpose: To investigate whether cavitation enhances the degree of coagulation during pulsed high-intensity focussed ultrasound (HIFU) in an isolated liver perfusion system. Methods: Isolated liver was treated by pulsed HIFU or continuous-wave HIFU with different portal vein flow rates. The cavitation emission during exposure was recorded, and real-time ultrasound images were used to observe changes in the grey scale. The coagulation size was measured and calculated. Results: HIFU treatment led to complete coagulation necrosis and total cell destruction in the target regions. Compared to exposure at a DC of 100%, the mean volumes of lesions induced by 6 s exposure at DCs of 50% and 10% were significantly larger (P < .01) but were smaller at a DC of 5%. The necrosis volume was negatively related to the perfusion rate in the pulsed HIFU at a DC of 50% for exposure durations of 4 and 6 s, while the perfusion flow rate did not affect the necrosis volume for exposure durations of 1, 2 and 3 s. For increased perfusion flow rates, there was no significant decrease in the cavitation activity for the pulsed-HIFU (P > .05). For continuous-wave HIFU exposure, there was a significant decrease in the necrosis volume the cavitation activity for exposure times of 1, 2, 3, 4, and 6 s with increasing portal perfusion rates. Conclusion: Perfusion flow rates negatively influence cavitation activity and coagulation volume. Ablation is significantly enhanced during pulsed HIFU exposure compared with continuous-wave HIFU.